Correction: The structuring effect of the alkyl domains on the polar network of ionic liquid mixtures: a molecular dynamics study. Issue 45 (9th November 2022) - Mazzilli, Valerio; Wang, Yanting; Saielli, Giacomo
Abstract : Correction for 'The structuring effect of the alkyl domains on the polar network of ionic liquid mixtures: a molecular dynamics study' by Valerio Mazzilli et al., Phys. Chem. Chem. Phys., 2022, 24, 18783–18792, ; https://doi.org/10.1039/D2CP02786K .